2017
DOI: 10.1016/j.ntt.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

PCBs and measures of attention and impulsivity on a continuous performance task of young adults

Abstract: The present study examines the relationship between current body burden of persistent PCBs and attention and impulsivity in 140 Akwesasne Mohawk young adults aged 17 to 21 whose environment has been contaminated by industrial effluent. Attention and impulsivity were measured by errors of omission, errors of commission, and patterns of reaction time responses on the Conners Continuous Performance Test. The PCB measure was the sum of those persistent PCB congeners detected in 50% of the participants. After adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 70 publications
(122 reference statements)
1
6
0
Order By: Relevance
“…Finally, Sagiv and colleagues also linked gestational PCB exposure with ADHD-like symptomatology in children, although this seems to be more strongly associated with attentional traits than the inhibitory control dimension, particularly in boys (Sagiv et al, 2010, 2012). Similar results were found in a recent study conducted by Behforooz et al (2017). The results of this study revealed a positive correlation between PCB exposure rates and altered attention in young male adults, with no significant effects regarding impulsive domains (Conner's CPT-II), like other previous studies (Ethier et al, 2015).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, Sagiv and colleagues also linked gestational PCB exposure with ADHD-like symptomatology in children, although this seems to be more strongly associated with attentional traits than the inhibitory control dimension, particularly in boys (Sagiv et al, 2010, 2012). Similar results were found in a recent study conducted by Behforooz et al (2017). The results of this study revealed a positive correlation between PCB exposure rates and altered attention in young male adults, with no significant effects regarding impulsive domains (Conner's CPT-II), like other previous studies (Ethier et al, 2015).…”
Section: Resultssupporting
confidence: 93%
“…In human studies, a total of 14 studies analyzed impulsive outcomes in relation to different PCB congeners, 1 (7%) of them was labeled as high (Ethier et al, 2015) and the remaining 13 (93%) as medium-high (Jacobson and Jacobson, 2003; Stewart et al, 2003, 2005, 2006; Vreugdenhil et al, 2004; Plusquellec et al, 2010; Sagiv et al, 2010, 2012; Boucher et al, 2012a,b; Verner et al, 2015; Behforooz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, PCBs have been associated with altered methylation of genes involved in autism spectrum disorder (Mitchell et al, 2012; Dunaway et al, 2016). Epidemiologic studies have also reported on PCB exposures and reduced attention and impulsivity (Behforooz et al, 2017; Rosenquist et al, 2017b), as well as mood disorders in adults (Gaum et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PCBs and their metabolites are known to efficiently transfer from maternal to foetal blood via the placenta ( 268 , 269 ) and to nursing children via milk ( 270 , 271 ). Prenatal PCB exposure in human has been associated with increased risk of a number of TH-related disorders including, high BMI ( 272 ), IQ loss ( 273 , 274 , 275 ), cognitive defects ( 23 , 273 , 276 , 277 , 278 ), reduced visual recognition memory ( 274 ), attention and motor deficits ( 276 , 279 , 280 , 281 ), increased risk of autism ( 282 , 283 ) and ADHD ( 273 , 284 , 285 ). In PCB-exposed adults, an increased risk of cardiovascular disease has been reported ( 286 ), as has a slightly increased risk of thyroid autoimmunity in men ( 287 , 288 ).…”
Section: Polychlorinated Biphenyls (Pcbs)mentioning
confidence: 99%